The moral project of childhood motherhood, material life, and early children's consumer culture - Cook, Daniel Thomas 1961- (New York University Press, 2020)
""The Moral Project of Childhood" explores the topics of motherhood and early children's consumer culture"--
Includes bibliographical references and index
Keywords: Geschichte 1800-1899; Erziehung; Kind; Verantwortung; Mutter; USA; Motherhood; Child consumers; Consumers; SOCIAL SCIENCE / Sociology / General